SPE Annual Technical Conference and Exhibition 1997
DOI: 10.2118/38653-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Procedure to Integrate Well Test Data, Reservoir Performance History and 4-D Seismic Information into a Reservoir Description

Abstract: This paper deals with the problem of estimating the distributions of permeability and porosity in heterogeneous and multiphase petroleum reservoirs by matching the dynamic behavior. The dynamic data is in the form of field measurements from well testing, production history, interpreted 4-D seismic information, and other data such as correlations between permeability and porosity, geostatistics in the form of a variogram model and the inference of large scale geological structure. The issue was posed as an inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(59 citation statements)
references
References 26 publications
(15 reference statements)
0
59
0
Order By: Relevance
“…This algorithm is based on the Gauss-Newton algorithm. Details concerning the implementation were reported in previous work 1,2,3 . d) Interfaces for the above modules.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This algorithm is based on the Gauss-Newton algorithm. Details concerning the implementation were reported in previous work 1,2,3 . d) Interfaces for the above modules.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work 1,2,3 it has been demonstrated that it is possible to compute the derivatives of the primary variables of an implicit numerical simulator with respect to any kind of parameter by using Eqn. 1.…”
Section: Mathematical Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…As soon as 4D seismic is also considered, advanced workflows must be designed to incorporate both production and seismic data in a consistent way. The improvements in the quantitative processing of 4D seismic motivated many works about this topic (Landa and Horne, 1997;Pianelo et al, 2000;Gosselin et al, 2001;Waggoner et al, 2002;Stephen and McBeth, 2006;Roggero et al, 2007;. However, there is still no definite matching methodology and several issues remain to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (1997) used amplitude difference or other seismic attributes difference while Arenas et al (2001) used velocity difference. Landa and Horne (1997) assumed that saturation changes could be obtained directly from time-lapse surveys.…”
Section: Introduction To Time-lapse Seismic Datamentioning
confidence: 99%